THERAPEUTIC POTENTIAL OF GLP-1 RECEPTOR AGONISTS IN ALZHEIMER’S DISEASE: INSIGHTS FROM PRECLINICAL AND CLINICAL EVIDENCE - Lidia Jurczenko; Dominika Walczak; Katarzyna Jakubowska; Aleksandra Miśta; Aleksander Białoń; Igor Gawłowski; Aleksandra Dorosz; Adrian Kruk; Weronika Ewa Nowak; Paweł Harbut (International Journal of Innovative Technologies in Social Science, 2025)
Alzheimer’s disease is a multifactorial neurodegenerative disorder characterized by progressive cognitive decline and complex pathological mechanisms involving amyloid-β accumulation, tau hyperphosphorylation, oxidative stress, and metabolic dysfunction. Glucagon-like peptide-1 receptor agonists (GLP-1RAs), originally developed for type 2 diabetes, have recently emerged as promising candidates for disease modification in AD due to their broad neuroprotective and metabolic actions.This review synthesizes evidence from molecular studies, animal models, and early clinical trials to evaluate the therapeutic potential of GLP-1RAs in AD. In animal models, agents such as liraglutide, exenatide, and semaglutide consistently improve learning and memory performance, reduce amyloid and tau pathology, attenuate neuroinflammation, and restore mitochondrial and synaptic function. Mechanistically, these effects are mediated through modulation of the PI3K/Akt/GSK-3β, ERK, and cAMP/CREB signaling pathways, normalization of insulin signaling, and enhancement of neuronal and glial resilience.Early clinical studies suggest that GLP-1RAs may slow cognitive decline and brain atrophy in individuals with mild or moderate AD, although sample sizes and follow-up durations remain limited. Ongoing large-scale Phase III trials with semaglutide and liraglutide are expected to clarify their clinical efficacy. Collectively, current findings indicate that GLP-1RAs offer a multifaceted approach to counteract AD pathology by integrating metabolic, neurotrophic, and anti-inflammatory mechanisms, representing a potential shift toward metabolism-targeted disease-modifying therapies.